Analisis Tingkat Kepuasan Pengguna Aplikasi Moovit pada Layanan Transportasi Transjakarta Menggunakan Metode Enhanced Information System Success Model - Seftya Ayu Pratiwi; Anik Hanifatul Azizah (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2026)
This study aims to analyze the level of user satisfaction with the Moovit application in TransJakarta transportation services using the Enhanced Information System Success Model (EISSM). The Moovit application is a technology-based information system that provides route guidance, real-time bus arrival estimates, and integrated information on various transportation modes to support user mobility. Data were collected through the distribution of questionnaires using a Likert scale to 100 respondents selected through the Slovin sampling method. The collected data were analyzed using SmartPLS 4 to examine the validity, reliability, and relationships among variables within the EISSM framework. The results indicate that most respondents have a positive perception of the effectiveness of the Moovit application, although several variables remain at a neutral level. The application of the EISSM model reveals that not all indicators meet the criteria for validity and reliability, indicating that certain variables require improvement. Hypothesis testing shows that 9 out of 14 proposed hypotheses are statistically significant. The variables of information quality, system quality, and service quality are found to have a significant effect on user satisfaction with the Moovit application. However, some relationships between variables are not significant, such as the effect of information quality on trust and the effect of user satisfaction on net benefits. Based on these findings, it can be concluded that although the Moovit application is considered helpful for TransJakarta users, improvements in information accuracy, data update speed, and user interface usability are still necessary to enhance user satisfaction, trust, and overall user experience.